Enhancing Socio Economic Development Spurred Through STI Policy Framework Into the Nucleus Off Mainstream Society in Malaysia - Ariffin, Aini Suzana; Ismail, Syuhaida; Ali, Salum S. (Frontiers in Political Science, 2022)
Over the past decades, the South South Governments have sought to make innovation a key issue in their policy agendas as catalyst toward sustainable development. Many south south countries realized that innovation with the use of science and technology had a vast potential in the economic transformation of a nation and as means to economic growth. In formulating or implementing innovation policy, it is imperative to identify the possible gaps in the system and set the viable interventions in promoting innovation strategic focus. Looking at Malaysia, it can be said that the 10-10 MySTIE was introduced into the mainstream for the adoption into science, technology and innovation (STI). Their intentions were admittedly commendable, however the implementation process was wanting. Policies are the brainchild of a group of people who have adequate knowledge of the subject matter. The implementation roadmap must be clearly charted for any policy to take a life of its own. The common failing in most policies are that policies are well thought of, but a roadmap to realise the policy is seldom implemented and seldom monitored, hence many well intentioned policies fall by the wayside. For innovation policy to take shape, there is a need to commit to finance to realise the policy, where the systems must be in place, skilled labour must be made available and where necessary, lure foreign skills to participate in the policy implementation, who are the participants that are required and their availability. Every conceivable actor must be requested to be involved. In taking a critical view of the policy stage to implementation stage, the need to keep in mind the market segment is critical as innovation and its final product are aimed at attracting the market segment the innovation is targeting. Thus, this paper discusses in detail the enhancement of the socio economic development spurred through the STI policy framework into the nucleus off mainstream society towards the achievement of the aforementioned the 10-10 MySTIE framework.